Trade regulations and global production networks - Christoph Scherrer; Stefan Beck (International Labour Organization (ILO), 2016)
This study provides an overview of some, not all initiatives to improve working conditions throughout global production networks. On the basis of secondary sources it assesses the contribution of the instruments favored by these initiatives. It starts with an economic justification of international workers' rights. The debate about international workers' rights revolves primarily around enforcing standards in developing countries. Opponents of internationally enforced workers' rights see them as an obstacle to closing the industrial gap. They argue that better living and working conditions cannot be legislated but would be the natural outcome of industrialization.
Keywords: 330; trade agreement; workers rights; working conditions; value chains; role of ILO